2021
DOI: 10.1519/jsc.0000000000002709
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Interval vs. Continuous Endurance Training: Preventive Effects on Hormonal Changes and Physiological Adaptations in Prediabetes Patients

Abstract: Safarimosavi, S, Mohebbi, H, and Rohani, H. High-intensity interval vs. continuous endurance training: Preventive effects on hormonal changes and physiological adaptations in prediabetes patients. J Strength Cond Res XX(X): 000-000, 2018-The aim of this study was to examine the effects of a 12-week high-intensity interval training (HIIT) intervention, or an isocaloric continuous endurance training (CET) intervention on insulin resistance indices and change in irisin and preptin in patients with prediabetes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…The major findings of the current study were a significant decrease in preptin and a significant increase respectively, compared to CON, suggesting that the mechanisms of effect for hormonal alterations (i.e. preptin) are different depending on the volume and intensity of training (Safarimosavi et al, 2018). Hence, both HIIT and CETFAT regimens could be effective exercise protocols depending on the priority of specific physiological requirements (Safarimosavi et al, 2018).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The major findings of the current study were a significant decrease in preptin and a significant increase respectively, compared to CON, suggesting that the mechanisms of effect for hormonal alterations (i.e. preptin) are different depending on the volume and intensity of training (Safarimosavi et al, 2018). Hence, both HIIT and CETFAT regimens could be effective exercise protocols depending on the priority of specific physiological requirements (Safarimosavi et al, 2018).…”
Section: Discussionmentioning
confidence: 62%
“…preptin) are different depending on the volume and intensity of training (Safarimosavi et al, 2018). Hence, both HIIT and CETFAT regimens could be effective exercise protocols depending on the priority of specific physiological requirements (Safarimosavi et al, 2018). Furthermore, we found that there was a positive correlation between preptin and HOMA-IR, body mass and BMI.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A recent study of animals revealed a significantly higher increase in irisin after HIT when compared to CMT following an 8-week intervention; an effect that was ascribed to the higher reduction of cellular energy charge and ATP levels during HIT [35]. However, in patients with prediabetes (38.6 ± 4.5 years), Safarimosavi et al showed decreased irisin concentrations after both a 12-week HIT intervention and a CMT intervention with intervals performed at an exercise intensity of 90 % VO 2peak [31]. Overall, therefore, there is discrepancy in the literature in the direction of observed changes in irisin levels following exercise training.…”
Section: Discussionmentioning
confidence: 98%
“…Duration may be just one of them. Reductions in body mass and fat mass, that typically occur when exercise is performed over a longer period of time, are expected to accompany reductions in circulating irisin levels [28,31], as irisin can be released not solely from muscle tissue but also from adipose tissue [29]. However, it should be noted that skeletal muscle is the primary source for circulating irisin and only a small part (~28 %) is released by adipose tissue [29].…”
Section: Discussionmentioning
confidence: 99%